STRATEGI DOTS DALAM PROGRAM PENANGGULANGAN TUBERKULOSIS DI PUSKESMAS MATITI KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Hertati Nababan; Wisnu Hidayat; Mido Ester J. Sitorus; Netty Brahmana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Tuberculosis (TB) is a global public health problem caused by Mycobacterium tuberculosis and is one of the top 10 causes of death worldwide. DOTS is a very effective strategy to treat TB patients. One of the success factors for TB control is the availability of sufficient human resources, both in terms of quantity and quality. Objective to identify the implementation of the DOTS Strategy component in the TB control program at the Matiti Health Center, Doloksanggul District. This type of research is a qualitative research with analytical descriptive approach, through in-depth interviews and taking research subjects using purposive sampling method. The main foundation of this research is the phenomenology of design. There were eight informants in this study consisting of key informants, main informants and additional informants. Data analysis was carried out with three streams of activities that occurred simultaneously, namely data condensation, data display and conclusions: drawing and verifying. Result there is no political commitment in the form of local regulations. The TB program implementers at the Puskesmas have not been fully trained. Case finding has not been carried out actively, still and intensively. Case detection rate and success rate has not met the national indicators. Planning for the availability of OAT has been included with reference to the number of cases and the type of patient. PMO has contributed to the control of patient's drug ingestion. The SITB application has not been carried out optimally so that the evaluation of program implementation is not carried out properly. Conclusion Implementation TB control program at the Matiti Health Center is still not optimal and the coverage of patient findings is still low.